(untitled) (Revista Rupturas, 2017)
Traditional educational institutions are built on positivist paradigms whose objective is to maintain and perpetuate the system. A positivist approach suggests that the words body-mind are opposite and exclusive dualities. The so called New School of the XIX century provides an alternative to this traditional system of education which is still in use at institutions. The thinking and work of Ellen Key and María Montessori provide a new approach for the perception of the body at schools. Additionally, we present the methodological approach employed by the educational community at Centro Educativo Shekénuk. The educational community at this school assimilates the concept of body-mind with the purpose of sharing a vision of humans as wholistic and artistic beings.